Enhancing the performance of a vapour compression refrigerator system using R134a with a CuO/CeO2 nano-refrigerant - Mohamed, HudaElslam (Strojniški vestnik, 2022)
Most studies report that dispersing nanoparticles into refrigerants and lubricating oils leads to performance improvements in refrigeration systems, due to improvements in the thermal physics properties of a pure refrigerant, which leads to reduced energy consumption. Using nanoparticles in a refrigeration system is associated with many difficulties, such as the cost of preparing and obtaining a stable and homogeneous mixture with less agglomeration and sedimentation. Most current studies focus on the use of metals, metal oxides, and a hybrid of oxides as nanoparticles in refrigeration systems. In this research, nanoparticles were prepared in an inexpensive and easy way as a single oxide and as a mixture consisting of copper and cerium oxides. The results of nanoparticle preparation using X-ray diffraction and scanning electron microscopy prove that the particles of the samples were spherical in shape, with suitable average diameters ranging from 78.95 nm, 79.9 nm, 44.15 nm and 63.3 nm for copper oxide, cerium oxide, the first mixture, and the second mixture, respectively. Cerium oxide has not been used in a refrigeration system; this study preferred the implementation of a theoretical study using Ansys Fluent software to verify the possibility of improving the performance of the refrigeration system. The results confirmed that copper oxide enhanced the coefficient of performance of the refrigeration system by 25 %, and cerium oxide succeeded in improving the performance of the. system by a lesser value. The mixture containing a higher percentage of copper oxide yielded better results.
Keywords: coefficient of performances; hladilno število; kompresorski hladilni sistemi; nanodelci; nanohladiva; nanoparticles; nano-refrigerants; vapour compression refrigeration systems